Digital epidemiology of high-frequency search listening trends for the surveillance of subjective well-being during COVID-19 pandemic - Al-Kenane, Khalida; Boy, Frederic; Alsaber, Ahmad; Nafea, Rania; AlMutairi, Shihanah (Frontiers in Psychology, 2024)
The coronavirus disease (COVID-19) pandemic has led to a dramatic increase in online searches related to psychological distress. Governments worldwide have responded with various measures to mitigate the impact of the virus, influencing public behavior and emotional well-being. This study investigated the relationship between government actions and public reactions in terms of online search behaviors, particularly concerning psychological distress during the pandemic. The primary objective of this study was to analyze how changes in government policies during the COVID-19 pandemic influenced public expressions of psychological distress, as reflected in the volume of related online searches in Kuwait.Method: Utilizing Google Trends data, the study analyzed search frequencies for terms associated with psychological distress such as "anxiety" and "lockdown." The analysis correlated these search trends with government actions using the Oxford COVID-19 Government Response Tracker (OxCGRT). The study period covered March 1, 2020, to October 10, 2020, and involved extensive data collection and analysis using custom software in R programming.Results: There was a significant correlation between the stringency of government-imposed restrictions and the volume of online searches related to psychological distress. Increased searches for "lockdown" coincided with heightened government restrictions and were associated with increased searches for "anxiety," suggesting that policy measures significantly impacted public psychological distress.The study concludes that governmental responses to the COVID-19 pandemic, measured through OxCGRT, have a measurable impact on public psychological distress, as evidenced by online search behaviors. This underscores the importance of considering psychological impacts in policymaking and suggests further research to explore this dynamic comprehensively. Future studies should focus on refining the correlation between specific types of policy measures and different expressions of psychological distress to better inform public health strategies and interventions.